Applicataion of ormsby wavelet for generation of synthetic seismic signals - Sai Sumanth, E; Joseph, V; K S Ramesh, Dr; S Koteswara Rao, Dr (International Journal of Engineering and Technology, 2018)
Investigation of signals reflected from earthâ€™s surface and its crust helps in understanding its core structure. Wavelet transforms is one of the sophisticated tools for analyzing the seismic reflections. In the present work a synthetic seismic signal contaminated with noise is synthesizedÂ  and analyzed using Ormsby wavelet[1]. The wavelet transform has efficiently extracted the spectra of the synthetic seismic signal as it smoothens the noise present in the data and upgrades the flag quality of the seismic data due to termers. Ormsby wavelet gives the most redefined spectrum of the input wave so it could be used for the analysis of the seismic reflections.Â